Kruppel-like factor 15 is required for the cardiac adaptive response to fasting. - Keiki Sugi; Paishiun N Hsieh; Olga Ilkayeva; Shamanthika Shelkay; Bridget Moroney; Palvir Baadh; Browning Haynes; Megan Pophal; Liyan Fan; Christopher B Newgard; Domenick A Prosdocimo; Mukesh K Jain (PLoS ONE, 2018)
Cardiac metabolism is highly adaptive in response to changes in substrate availability, as occur during fasting. This metabolic flexibility is essential to the maintenance of contractile function and is under the control of a group of select transcriptional regulators, notably the nuclear receptor family of factors member PPARα. However, the diversity of physiologic and pathologic states through which the heart must sustain function suggests the possible existence of additional transcriptional regulators that play a role in matching cardiac metabolism to energetic demand. Here we show that cardiac KLF15 is required for the normal cardiac response to fasting. Specifically, we find that cardiac function is impaired upon fasting in systemic and cardiac specific Klf15-null mice. Further, cardiac specific Klf15-null mice display a fasting-dependent accumulation of long chain acylcarnitine species along with a decrease in expression of the carnitine translocase Slc25a20. Treatment with a diet high in short chain fatty acids relieves the KLF15-dependent long chain acylcarnitine accumulation and impaired cardiac function in response to fasting. Our observations establish KLF15 as a critical mediator of the cardiac adaptive response to fasting through its regulation of myocardial lipid utilization.